Study on Division of Flood Season of Wanquan RiverBasin in Hainan Island Based on Various Methods - XIAO Jing; YANY Xiangquan (Renmin Zhujiang)
The division of flood season is of great significance to flood prevention.This paper applies SPSScluster analysis, discriminant analysis and fuzzy statistical test for the division of floodseason and non-flood season in Wanquan River Basin.Discriminant analysis takes into account the time series of samples, so it is superior to clusteranalysis. The fuzzy statistical test is sensitive to the selected factors, and the division resultwith flow as the factor is better than that with rainfall as the factor. The results of SPSScluster analysis, discriminant analysis and fuzzy statistical test with flow as factor aresimilar, which can be used in practice. For the convenience of practical work, it is suggestedthat the flood season should be from early May to late November and the non-flood season should befrom early December to late April of the following year in Wanquan River Basin.